Non-agriculturalization of cultivated land in densely populated areas at the watershed scale: a case study of the Minjiang River Basin, China - Xi Zhao; Zhongwen Hu; Yinghui Zhang; Jingzhe Wang; Tiezhu Shi; Yanguo Liu; Jie Zhang; Guofeng Wu (PeerJ, 2025)
Zero hunger is a top priority in the Sustainable Development Goals, however, millions of people worldwide still face hunger. Over the years, China has experienced rapid population growth, industrialization and urbanization, leading to significant agricultural land loss, which threats the nation’s food supply. Understanding the patterns and driving factors of non-agriculturalization is crucial for its protection. The Minjiang River Basin, the largest tributary of the Yangtze River, is densely populated and experiencing rapid urbanization, making it a typical snapshot of the non-agriculturalization in China. This study comprehensively examines the characteristics and trends in the spatiotemporal evolution of cultivated land in the Minjiang River Basin, along with the drivers of non-agriculturalization. The results reveal the findings: (1) From 1990 to 2020, the cultivated land in the Minjiang River Basin has decreased and mainly concentrated in flat areas. The spatiotemporal evolution of cultivated land exhibits low dispersion and strong directionality, predominantly shifting northward, and the migration of cultivated land can be divided into three stages. (2) A consistent positive spatial correlation is observed in the non-agriculturalization areas of cultivated land in the Minjiang River Basin, with high-high (HH) clustering analysis revealing an aggregation pattern radiating outward from the city center. (3) Population growth and economic factors are the primary drivers of non-agriculturalization in the Minjiang River Basin.